ANALISIS KINERJA MANAJEMEN RISIKO PEMBIAYAAN DAN PENGARUHNYA TERHADAP RETURN ON ASSET (ROA) PADA PT BANK SYARIAH MANDIRI - Rengga Kusumah; Umar Burhan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to determine how the development of the quality of financing risk management performance in PT Bank Syariah Mandiri represented by Non Performing Financing (NPF) profit sharing principle and Non Performing Financing (NPF) non-profit sharing principle. This study is also to determine the effect of the quality of financing risk management performance against Return on Assets (ROA) in PT Bank Syariah Mandiri. ROA is more appropriately used to measure performance or achievements that are affected by the NPF, because one of the elements ROA is financing. Data analysis method used in this research is multiple linear regression analysis. These results indicate that the quality of the risk management performance of PT Bank Syariah Mandiri decreased. Then NPF profit sharing principle has no effect on ROA, while NPF non-profit sharing principle has a negative effect on ROA. Keywords: Financing Risk Management, Return on Assets (ROA), Non Performing Financing (NPF)